2019
DOI: 10.3390/nu11061213
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Inflammatory Index and Odds of Colorectal Cancer and Colorectal Adenomatous Polyps in a Case-Control Study from Iran

Abstract: Background: Chronic inflammation is implicated in the development of colorectal cancer (CRC) and its precursor; colorectal adenomatous polyps (CAP). Some dietary factors are important triggers for systemic inflammation. Therefore, the present study aimed to investigate the association between the dietary inflammatory index (DII®) and the risk of CRC and CAP in an Iranian case-control study. Methods: 134 newly diagnosed CRC patients, 130 newly diagnosed CAP patients, and 240 hospitalized controls were recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 56 publications
5
24
1
Order By: Relevance
“…The present study provides evidence regarding the association between a higher E-DII score and an increased risk of colorectal cancer in a Chinese population. In concordance with this result, previous epidemiologic studies observed significant positive association between the DII and colorectal cancer risk [20][21][22][23][24][25][26][27][28][29][30][31][32][33]. A 2017 meta-analysis of four prospective cohort studies and five case-control studies also reported an overall 40% increased risk of colorectal cancer in the highest quartile of the DII score [44], a result consistent with what we found.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study provides evidence regarding the association between a higher E-DII score and an increased risk of colorectal cancer in a Chinese population. In concordance with this result, previous epidemiologic studies observed significant positive association between the DII and colorectal cancer risk [20][21][22][23][24][25][26][27][28][29][30][31][32][33]. A 2017 meta-analysis of four prospective cohort studies and five case-control studies also reported an overall 40% increased risk of colorectal cancer in the highest quartile of the DII score [44], a result consistent with what we found.…”
Section: Discussionsupporting
confidence: 92%
“…To date, five prospective cohort studies [20][21][22][23][24] and nine case-control studies [25][26][27][28][29][30][31][32][33] have investigated the association between the DII and colorectal cancer risk, and all of them have found that a higher DII score is associated with an increased risk of colorectal cancer. Four [30][31][32][33] of nine case-control studies were conducted in Asian countries, including South Korea, Jordan, and Iran. However, to the best of our knowledge, no study has been conducted in Chinese population, whose socio-demographic characteristics and dietary patterns that are characterized mainly by higher consumption of vegetables, rice and fish/sea food vary from those of other populations [34].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, direct comparison to other E-DII/DII quantile categorizations is challenging: Most of the studies assessed the inflammatory potential of the diet using the DII (energy was included in the score or as a covariate in final models); depending on the study, the E-DII/DII score was estimated including different number of food/nutrient parameters; other approaches have been used to estimate E-DII besides the one published by Shivappa et al [44]; and only a few studies presented sex-specific E-DII/DII values. Despite these limitations, our E-DII range values in men are wider than the ones reported by the case-control study in Iran [73]. In women, our E-DII values are slightly lower than the ones reported by the case-control study in Germany; however, that study only included postmenopausal women [32].…”
Section: Discussioncontrasting
confidence: 71%
“…Therefore, it is not surprising that we have observed consistently strong positive relationships between the DII score and CRC. At this juncture, there are 13 papers published by our group on CRC incidence [42,78,79,80,81,82,83,84,85,86,87,88,89] from studies carried out in various populations across the world [81,82].…”
Section: DII and Cancersmentioning
confidence: 99%